Effect of polybrominated diphenyl ether congeners on placental cytokine production. (February 2018) - Arita, Yuko; Yeh, Corinne; Thoma, Theodosia; Getahun, Darios; Menon, Ramkumar; Peltier, Morgan R.
Highlights: PBDEs are common pollutants that have been previously linked to preterm birth. PBDEs exist as 209 different congeners with different tissue distributions. We compared 5 common PBDE congeners for effects on placenta cytokine production. Production of biomarkers was altered in a congener and infection-dependent manner. Abstract: Polybrominated diphenyl ethers (PBDEs) are pollutants that may increase the risk of preterm birth. In previous studies, we found that a mixture of PBDEs altered the expression of biomarkers for preterm birth by the placenta. However, there are 209 different PBDE congeners with different tissue distributions. How these different congeners may alter the production of immunomodulators by the placenta that help to maintain the survival of the fetal allograft is unclear. Therefore, we compared the effects 5 common congeners on basal and bacteria-stimulated cytokine production by the placenta. Placental explant cultures were incubated with 20 μM of PBDE congeners 47, 99, 100, 153, 209 or vehicle in the presence and absence of Escherichia coli for 20 h. Conditioned medium was harvested and concentrations of IL-1β, TNF-α, IL-6, sgp130, HO-1, IL-10, BDNF, and 8-IsoP quantified. For unstimulated cultures, all congeners, except for PBDE-47, reduced the production of IL-1β and IL-6 production was enhanced by PBDE-153. BDNF concentrations tended to be reduced by most PBDE congeners and IL-10 production was enhanced by PBDE-99, −153, and −209. 8-IsoP production was enhanced by PBDE-153, but not the other congeners. For bacteria-stimulated cultures, PBDE-47 increased IL-1β production and PBDE-47, −153, and −209 tended to reduce TNF-α production. IL-6 production was enhanced by all PBDEs except 153. IL-10 production was enhanced by all congeners except for PBDE-47. All congeners significantly enhanced BDNF and 8-IsoP. These results suggest that PBDEs can alter the expression of placental biomarkers in a congener and infection-dependent manner.